Analysis of Prabowo Subianto's First Speech as Indonesia’s President-Elect (2024): Critical Discourse Analysis - Muhibbun, Akhmad; Priyadarshani, Hewawasam Epalawattage Niluka (Indonesian Scientific Publication, 2024)
The political contest in the 2024 election has resulted in the winning result of candidate pair number two, namely the pair Prabowo Subianto and Gibran Rakabuming Raka. After the announcement of the election results by the KPU, the elected couple delivered a victory speech. This research aims to explain the macro, superstructure, and micro structure in Prabowo Subianto's first speech after being declared the winner in the 2024 presidential election. This research also demonstrates the social aspects (societal analysis) that shape speech discourse. This qualitative research uses a critical discourse analysis approach modeled by Teun A. Van Dijk. The data is in the form of Prabowo Subianto's speech expressions. The data source was obtained via YouTube Kompas.com. The sampling technique was carried out using purposive sampling. The data collection technique was carried out by document analysis. Data analysis was carried out using interactive data analysis. Triangulating theory, data sources, and between researchers carried out the data validity test. The research results show that macrostructure, superstructure, and microstructure loads are present. Macro structure regarding expressions of gratitude for the implementation of the election process. The superstructure consists of an opening, content, and closing scheme. Microstructure consists of semantics, syntax, stylistics, and rhetoric. Hopefully, this research can enrich the scientific knowledge of critical discourse studies and their use.